TEACHERS AND STUDENTS’ LIVED EXPERIENCES IN THE IMPLEMENTATION OF SPIRAL PROGRESSION APPROACH IN MATHEMATICS - Lazaro, Cristina (International Journal of Arts, Sciences and Education, 2023)
ABSTRACT Employing the methodology of descriptive phenomenology, this research investigated the perspectives and firsthand experiences of teachers and students regarding the adoption of the spiral progression approach (SPA) in teaching and learning mathematics. The study involved participants from junior high schools within the Division of Tuguegarao City. The findings indicated a varied range of viewpoints regarding the effectiveness of the SPA in mathematics instruction. While some individuals held a positive view, recognizing its merits and positive impact, others expressed skepticism and identified challenges associated with its implementation. The experiences of both teachers and students in the domain of mathematics education were characterized by difficulties, shaped by curriculum, teacher, student, and school-related factors. Remarkably, the successful integration of the SPA into mathematics education was strongly influenced by the presence of a supportive school culture, comprised of essential elements that collectively fostered an environment conducive to effective SPA implementation and enhanced learning outcomes. The insights obtained from the lived experiences of teachers and students provide valuable insights for educators and policymakers to make well-informed decisions and adjustments, aiming to maximize the benefits and mitigate the limitations of utilizing the SPA in mathematics education.